Segregation at stacking faults within the γ′ phase of two Ni-base superalloys following intermediate temperature creep. (1st January 2015) - Viswanathan, G.B.; Shi, R.; Genc, A.; Vorontsov, V.A.; Kovarik, L.; Rae, C.M.F.; Mills, M.J.
Abstract : Using state-of-the-art energy dispersive spectroscopy, it has been established for the first time that there exists significant compositional variation (enrichment of Co and Cr and deficiency of Ni and Al) associated with superlattice intrinsic stacking faults created in the ordered γ′ precipitates following intermediate temperature deformation of two commercial superalloys. The results indicate that long range diffusion of these elements is intimately involved in the precipitate shearing process and is therefore closely linked to the time-dependent deformation of the alloys.